Dificultad en el proceso léxico, fluidez de la lectura y el proceso léxico ortográfico de la escritura en un estudio de caso de un niño de segundo grado del nivel primaria - Camogliano Huapaya, Carol Yemina (2023)
The objective of this case study was to design an evaluation and intervention plan presented by an 8-year-old boy, with difficulty in the lexical process, reading fluency and orthographic lexical process of writing. The following evaluation instruments were used for their learning profile: Metalinguistic Skills Test (THM), Naming Speed Test (ALE), LEE Test, PEABODY, TOMAL, ITPA, FROSTING DTVP -2, PECO and Test of Perception of Differences (CARAS-R).The instrumental factors of reading and writing were intervened. And improvement in reading was evidenced, through the correct association of the letter with its respective sound. In the lexical processes, there were achievements in the phonological route, when carrying out phoneme analysis and synthesis tasks; as well as accurately read words containing the letter "m", "n", "g", "j" and with syllables "gue" and "gui". In the visual route, he improved in reading bisyllabic and trisyllabic words with the syllable structure CV, CCV, CVC.Improved the interpretation of punctuation marks when reading sentences and texts according to the grade in which it is found. In writing, in the orthographic lexical process, he improved in the phonological route, by correctly using the RCGF and showing greater precision in his writing; while, in the visual route, he was able to use the orthographic lexical store, correctly writing words with gue, gui /, ga, go, gu.